A new species of Neojobertia Baill. (Bignonieae, Bignoniaceae) from Brazil - Faria, Jair Eustáquio Quintino; Zanatta, Maria Rosa Vargas; de Souza, Luzia Francisca; Proença, Carolyn Elinore Barnes (Phytotaxa, 2016)
A new species of Neojobertia is described from Brazil, Neojobertia alboaurantiaca. With the inclusion of this new species into the genus, Neojobertia includes three species, all of which are endemic to Brazil. Neojobertia alboaurantiaca grows predominantly in savannas and occurs in four neighbouring Brazilian states, Maranhão, Piauí, Goiás and Tocantins. In this study, we describe the new species, its habitat, distribution and evaluate its conservation status, as well as present a distribution map, illustrate key features and discuss the morphological features that distinguish it from Neojobertia mirabilis. The conservation status of the species has been evaluated as EN (endangered).